Rob Roy [videorecording (DVD)] - Caton-Jones, Michael; Neeson, Liam; Lange, Jessica; Hurt, John, 1940-2017; Roth, Tim; Stoltz, Eric, 1961-; Cox, Brian, 1946- (MGM/UA Home Video, 1998)
When a harsh winter threatens the majestic Scottish Highlands, Rob Roy MacGregor is forced to borrow money from the less-than-noble Marquis of Montrose to provide for his clan. When Montrose's evil henchmen conspire to take the wealth for themselves, they thrust Rob into the most challenging battle of his life.